"You're Missing Out on Something Great": Patient and Provider Perspectives on Increasing the Use of Cognitive Behavioral Therapy for Insomnia. Issue 3 (3rd May 2020) - Koffel, Erin; Amundson, Erin; Polusny, Grace; Wisdom, Jennifer P.
ABSTRACT: Objective/Background : Cognitive behavioral therapy for insomnia (CBT-I) is the most effective treatment for insomnia but is severely underutilized. One of the key reasons for underuse is lack of knowledge among patients and primary care providers, but effective methods and materials for increasing knowledge are unknown. This study conducted in-depth interviews with CBT-I patients and their CBT-I providers to explore their perceptions on increasing utilization of CBT-I. Participants : Participants included patients who had engaged in CBT-I ( N = 17) and CBT-I providers ( N = 7). Methods : Semistructured interviews were used to explore the CBT-I referral process, recommendations for increasing uptake of CBT-I, and opinions on CBT-I self-management, with thematic analysis used to identify conceptual themes. Findings were compared and contrasted across patients who completed versus prematurely discontinued therapy and patients versus CBT-I providers. Results : Three main themes of referral, selling, and delivery were identified. Regarding referral, patients had not heard of nor requested CBT-I. Proactive outreach is crucial in populations in which insomnia is so common that it becomes normalized. For selling, patients and CBT-I providers had powerful testimonials that could be used to "sell" treatment using a peer-to-peer approach. Finally, for delivery, patients and CBT-I providers were ambivalent about alternative delivery formats and emphasized the need for personal contact. Although technology may be useful in advertising and delivering CBT-I, it will be important to ensure that these approaches promote rather than discourage engagement in CBT-I. Conclusions : These findings suggest promising opportunities to increase the use of CBT-I, including direct-to-consumer marketing.